Effects of immediate postpartum contraceptive counseling on long-acting reversible contraceptive use in adolescents - Kaewkiattikun K (Dove Medical Press, 2017)
Kasemsis Kaewkiattikun Department of Obstetrics and Gynecology, Faculty of Medicine Vajira Hospital, Bangkok, Thailand Background: Adolescent pregnancy is a global public health problem, particularly repeated pregnancy. The best strategy to lower prevalence of adolescent pregnancy and repeated pregnancy is promoting highly effective long-acting contraceptive methods along with special counseling programs. Long-acting reversible contraception (LARC) is the ideal contraceptive of choice for adolescents. It is not known whether immediate postpartum contraceptive counseling increases postpartum LARC use in adolescents.Objective: To compare LARC use between immediate and conventional postpartum contraceptive counseling and discover predictive factors of postpartum LARC use.Materials and methods: This prospective, randomized controlled trial was conducted among postpartum adolescents at Department of Obstetrics and Gynecology, Faculty of Medicine Vajira Hospital, Navamindradhiraj University, Bangkok, Thailand, from 1 July 2016 to 31 March 2017. The participants were assigned to receive immediate postpartum contraceptive counseling or conventional postpartum contraceptive counseling. The primary outcome was postpartum LARC use. The secondary outcome was predictive factors for LARC use in postpartum adolescents.Results: Of the 233 postpartum adolescents, postpartum LARC use was 87 of 118 (73.7%) in the immediate postpartum counseling group and 49 of 115 (42.6%) in the conventional postpartum counseling group (odds ratio 3.780, 95% CI 2.18–6.57, p<0.001). A significant predictive factor for LARC use in postpartum adolescents was immediate postpartum counseling (odds ratio 3.67, 95% CI 2.10–6.41, p<0.001).Conclusion: Immediate postpartum contraceptive counseling led to a significant increase in postpartum use of LARC in adolescents, when compared with conventional (4–6 weeks) postpartum contraceptive counseling. Adolescent mothers who received immediate postpartum counseling were 3.67 times more likely to use LARC than those who received conventional postpartum counseling. Keywords: long-acting reversible contraception (LARC), adolescent, contraception, contraceptive counseling, immediate postpartum contraceptive counseling